Retro-rectal mass: a clinical dilemma; report of three cases with brief review of literature - Kant, Kamal; Singh, Kapisoor; Rathod, Yashpal Singh; Purohit, Richa (International Surgery Journal, 2018)
Retro rectal or presacral tumors are uncommon lesions. It can be difficult to diagnose as presenting signs and symptoms are usually nonspecific. Retro rectal lesions can be congenital or acquired, benign or malignant. Children can also have retro rectal masses like anterior meningocele, teratomas or cystic teratomas. FNAC or biopsy usually is not required as imaging can provide a reasonably good diagnosis. Cross-sectional imaging is essential in evaluating these lesions to determine the optimal surgical approach and the extent of resection. Surgery is the mainstay of treatment as it establishes the diagnosis and prevents the adverse consequences associated with malignant degeneration and secondary bacterial infection. The outcomes for patients with benign presacral tumors are favourable.